Evaluating Production of Cyclopentyl Tetraethers by Marine Group II Euryarchaeota in the Pearl River Estuary and Coastal South China Sea: Potential Impact on the TEX86 Paleothermometer - Wang, Jin-Xiang; Xie, Wei; Zhang, Yi Ge; Meador, Travis B.; Zhang, Chuanlun L. (Frontiers in Microbiology, 2017)
TEX86 is built upon an empirically observed correlation between ring distribution of glycerol dialkyl glycerol tetraethers (GDGTs) and sea surface temperature. According to cultural and environmental studies, Marine Group I (MG-I) Thaumarchaeota are hypothesized to constitute the dominant source of TEX86-related GDGTs in the ocean. Recently, Marine Group II (MG-II) Euryarchaeota are suggested to contribute significantly to the GDGT pool in the ocean. However, due to the absence of MG-II cultures, little is known regarding the potential impact of MG-II Euryarchaeota-derived GDGTs on TEX86 in the water column and ultimately its export to the sediment. In this study, we assessed the relationship between distributions of intact polar lipids (IPLs) and core GDGTs and MG-II Euryarchaeota and evaluated its potential effect on the TEX86 proxy. Lipid and DNA analyses were performed on suspended particulate matter and surface sediments collected along a salinity gradient from the lower Pearl River (river water) and its estuary (mixing water) to the coastal South China Sea (SCS, seawater). TEX86-derived temperatures for both IPL- and core-GDGTs from the water column and surface sediments were significantly correlated and both were lower than satellite-based temperatures. The ring index (RI) values in these environments were higher than predicted from the calculated TEX86-RI correlation, indicating that the GDGT pool in the water column of the PR estuary and coastal SCS comprises relatively more cyclopentane rings, which thereby altered TEX86 values. Furthermore, the 16S rRNA gene abundance of MG-II Euryarchaeota in the mixing water was two to three orders of magnitude higher than those observed in the river or seawater. Significant linear correlations were observed between the gene abundance ratio of MG-II Euryarchaeota to total archaea and the fractional abundance of phosphatidic IPL-GDGTs with cyclopentane rings. Collectively, these results corroborate previous studies that have shown that MG-II Euryarchaeota likely produce GDGTs with 1–4 cyclopentane moieties, which may bias TEX86 values in the water column and sediments. As such, valid interpretation of TEX86 values in the sediment record, particularly in coastal oceans, should consider the contribution from MG-II Euryarchaeota.